Ocular Manifestations of IBD: Pathophysiology, Epidemiology, and Iatrogenic Associations of Emerging Treatment Strategies - Holly Richardson; Giho Yoon; George Moussa; Aditi Kumar; Philip Harvey (Biomedicines)
Inflammatory bowel disease (IBD) is a complex, multisystemic disease and is associated with ocular pathology in 4–12% of patients. In general, ocular disease affects Crohn’s patients more frequently than those with ulcerative colitis. Episcleritis and uveitis are the most common presentations, with episcleritis often correlating with IBD flares, whereas uveitis presents independently of IBD activity and, in some cases, may even alert clinicians to a new diagnosis of IBD. Corneal EIMs encompass a range of pathologies, such as the common and benign keratoconjunctivitis sicca (dry eye disease), which nevertheless causes significant patient discomfort, and the rarer condition of peripheral ulcerative keratitis, which warrants urgent review due to the risk of corneal perforation. Alongside EIMs, clinicians should also be aware of the iatrogenic consequences to the eye following treatment of IBD. Corticosteroids may cause cataracts, glaucoma, and—indirectly via hyperglycaemia—diabetic retinopathy. Methotrexate is irritating to ocular tissues and may cause conjunctivitis and blepharitis. Biologic medications, such as anti-TNFα agents, overlap in their use as treatment of both IBD and uveitis, and yet in some patients may also increase the risk of acute uveitis flares, as well as opportunistic, sight-threatening infections. With integrated care between gastroenterology and ophthalmology, patient outcomes can be improved by facilitating earlier detection and management of ocular disease. This narrative review summarises the ocular extraintestinal manifestations of IBD, including pathophysiology, epidemiology, and current treatment strategies.